Effect of Zn addition and natural aging on the microstructure and mechanical properties of secondary AlSi7Cu2 alloys. Issue 1 (1st January 2023) - Scampone, G; Gursoy, O; Brutti, S; Timelli, G
Abstract: The effect of different Zn contents on the microstructure of a secondary AlSi7Cu2 alloy has been studied. The mechanical properties of the alloy during natural aging has been investigated too. The Zn additions range from 0.7 to 8 wt.%, and the tensile testing has been carried out at the as-cast condition and after 3, 7, 12 and 21 days of natural aging. Metallographic and image analysis techniques have been used to characterize the microstructural changes of the alloy. The results indicate that the alloy is strengthened as a function of the aging time and Zn addition. Both yield stress and elongation to fracture tend to stabilize over long aging times, independently of Zn level. The steady-state tensile properties are achieved earlier by increasing the Zn content. Furthermore, high Zn contents promote the formation of eutectic structure and the precipitation of needle-like Fe-rich compounds, which decrease the ductility of the material.